Increased Abundance of Tumour-Associated Neutrophils in HPV-Negative Compared to HPV-Positive Oropharyngeal Squamous Cell Carcinoma Is Mediated by IL-1R Signalling - Al-Sahaf, Sarmad; Hendawi, Naeima B.; Ollington, Bethany; Bolt, Robert; Ottewell, Penelope D.; Hunter, Keith D.; Murdoch, Craig (Frontiers in Oral Health, 2021)
The incidence of human papillomavirus (HPV)-associated cancer is increasing and HPV is now implicated in the aetiology of more than 60% of all oropharyngeal carcinomas (OPC). In OPC, innate immune cells such as neutrophils and macrophages generally correlate with poor prognosis, whilst adaptive immune cells, such as lymphocytes, tend to correlate with improved prognosis. This may, in part, be due to differences in the immune response within the tumour microenvironment leading to the recruitment of specific tumour-associated leukocyte sub-populations. In this study we aimed to examine if differences exist in the levels of infiltrated leukocyte sub-populations, with particular emphasis on tumour-associated neutrophils (TAN), and to determine the mechanism of chemokine-induced leukocyte recruitment by comparing HPV-positive and HPV-negative OPC. Immunohistochemical analysis showed that HPV-negative OPC contained significantly more neutrophils than HPV-positive tumors, whilst levels of CD68+ macrophages and CD3+ lymphocytes were similar. Using a 3D tissue culture model to represent tumour-stromal interactions, we demonstrated that HPV-negative tumour-stromal co-cultures expressed significantly higher levels of CXCL8, leading to increased neutrophil recruitment compared to their HPV-positive counterparts. Moreover, pre-treatment of these tumour-stromal models with the specific IL-1R antagonist, anakinra, dramatically reduced chemokine secretion and significantly impaired neutrophil and monocyte recruitment. Here, we identify a mechanism by which HPV-negative OPC may recruit more TAN than HPV-positive OPC. Since TAN are associated with poor prognosis in OPC, our study identifies potential therapeutic targets aimed at redressing the chemokine imbalance to reduce innate immune cell infiltration with the aim of improving patient outcome.